Evolutionarily Distant Streptophyta Respond Differently to Genotoxic Stress - Vágnerová, Radka; Lukešová, Alena; Lukeš, Martin; Rožnovská, Petra; Holá, Marcela; Fulnečková, Jana; Fajkus, Jiří; Angelis, Karel J (Genes, 2017)
Research in algae usually focuses on the description and characterization of morpho-and phenotype as a result of adaptation to a particular habitat and its conditions. To better understand the evolution of lineages we characterized responses of filamentous streptophyte green algae of the genera Klebsormidium and Zygnema, and of a land plant-the moss Physcomitrellapatens-to genotoxic stress that might be relevant to their environment. We studied the induction and repair of DNA double strand breaks (DSBs) elicited by the radiomimetic drug bleomycin, DNA single strand breaks (SSB) as consequence of base modification by the alkylation agent methyl methanesulfonate (MMS) and of ultra violet (UV)-induced photo-dimers, because the mode of action of these three genotoxic agents is well understood. We show that the Klebsormidium and Physcomitrella are similarly sensitive to introduced DNA lesions and have similar rates of DSBs repair. In contrast, less DNA damage and higher repair rate of DSBs was detected in Zygnema, suggesting different mechanisms of maintaining genome integrity in response to genotoxic stress. Nevertheless, contrary to fewer detected lesions is Zygnema more sensitive to genotoxic treatment than Klebsormidium and Physcomitrella.
Keywords: Klebsormidium; bleomycin; methyl methanesulfonate; Zygnema; Physcomitrella patens; DNA damage and repair; ultraviolet light